Interaction of nitrobenzoxadiazole derivatives of piperazine and aniline with bovine serum albumine in silico and in vitro - Faletrov, Yaroslav V.; Karpushenkova, Veronika S.; Zavalinich, Viktoryia A.; Yakovets, Polina S.; Shkredava, Anastasia D.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2021)
Albumin is a globular protein of plasma of mammalian blood participating in transport of hydrophobic metabolites and drugs. Thus, studies devoted to its binding are valuable as a part of evaluation of new potential drugs or fluorescent probes for in vivo usage. Here we describe results concerning synthesis and bovine serum albumin binding assay both in silico (docking) and in vitro (spectrophotometric and spectrofluorimetric titrations) for four new 7-nitrobenzoxadiazol-4-yl (NBD) derivatives of aniline and piperazine. Experimental dissociation constant for NBD-ethynylaniline 4 was calculated to be about 10 µmol/L.